(untitled) (Journal of Philosophy Culture and Political Science, 2026)
The article examines the role of state cultural policy as a tool for shaping national identity in the context of political transformations. The relevance of the study is обусловлена the increasing importance of the cultural sphere in ensuring social cohesion and societal stability during periods of institutional change, as well as the need to adapt cultural policy mechanisms to the challenges of globalization, digitalization, and the transformation of societal value orientations. The aim of the study is to identify the relationship between the instruments of state cultural policy and the level of cultural engagement of the population of the Republic of Kazakhstan. The methodological basis of the study consists of economic and statistical methods, including correlation and regression analysis, factor analysis (principal component method), as well as the calculation of a cultural engagement index. The information base includes official statistical data characterizing attendance at cultural institutions and the number of cultural events. The results of the study revealed a strong positive relationship between the number of events and attendance at cultural institutions, as well as a high explanatory power of the regression model. Factor analysis identified a dominant latent factor explaining 93.9% of the variation in indicators and reflecting the integral level of cultural engagement of the population. The calculated cultural engagement index demonstrated steady growth in the post-crisis period. It is concluded that state cultural policy in the Republic of Kazakhstan is implemented through the mechanism of expanding cultural activity, forming stable demand for cultural services and contributing to the strengthening of national identity. The practical significance of the study lies in the development of recommendations for improving the effectiveness of cultural policy in the context of modern political transformations. Keywords: national identity, public administration, cultural policy, cultural engagement